2019
DOI: 10.1080/14992027.2019.1660918
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivors treated with platinum-based chemotherapy affected by ototoxicity and the impact on quality of life: a narrative synthesis systematic review

Abstract: Cancer survivors treated with platinum-based chemotherapy affected by ototoxicity and the impact on quality of life: a narrative systematic review.Objective: To identify any change in quality of life (QoL) caused by chemotherapy-induced toxicities, such as hearing loss and tinnitus, to provide information in order to improve services and aid clinicians in their decisionmaking.Design: This systematic review followed the PRISMA checklist. The search terms were cancer, platinum-based chemotherapy, ototoxicity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 48 publications
(28 reference statements)
1
34
0
Order By: Relevance
“…More specifically, we tested whether cisplatin affects the period of the oscillations (the interval between two reference points), the phase (reflecting a change in the peak time of synchronous cell oscillations) and the amplitude (reflecting either a change in PER2 expression or altered synchrony). Cochlear explants from PER2::LUC reporter mice, cultured for a period of 6-9 days, were exposed for a duration of 3 days to six different doses of cisplatin (40,80,160, 400, 800, and 1600 nM), applied either at the trough of the oscillations at day 3 of the culture (day administration) or at the peak of the oscillations, at day 3.5 of the culture (night administration) in the absence of presynchronization. Day cisplatin treatment did not show any effect on PER2 rhythms on the amplitude (one-way ANOVA, F (6,27) = 0.794, P = .582), phase (one-way ANOVA, F (6,30) = 0.65, P = .69), and period (one-way ANOVA, F (6, 24) = 1.214, P = .333, Figure 5A-C).…”
Section: Per2::luc Rhythms Ex Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, we tested whether cisplatin affects the period of the oscillations (the interval between two reference points), the phase (reflecting a change in the peak time of synchronous cell oscillations) and the amplitude (reflecting either a change in PER2 expression or altered synchrony). Cochlear explants from PER2::LUC reporter mice, cultured for a period of 6-9 days, were exposed for a duration of 3 days to six different doses of cisplatin (40,80,160, 400, 800, and 1600 nM), applied either at the trough of the oscillations at day 3 of the culture (day administration) or at the peak of the oscillations, at day 3.5 of the culture (night administration) in the absence of presynchronization. Day cisplatin treatment did not show any effect on PER2 rhythms on the amplitude (one-way ANOVA, F (6,27) = 0.794, P = .582), phase (one-way ANOVA, F (6,30) = 0.65, P = .69), and period (one-way ANOVA, F (6, 24) = 1.214, P = .333, Figure 5A-C).…”
Section: Per2::luc Rhythms Ex Vivomentioning
confidence: 99%
“…In humans, there is evidence that patients with existing hearing deficits are more vulnerable to cisplatin ototoxicity. 13,40 Thus, auditory screens prior to cancer treatment could identify individuals at risk for greater auditory damage. This would be even more relevant in children, who show more severe ototoxicity compared to adults.…”
mentioning
confidence: 99%
“…Tinnitus was found to be more frequent in patients treated with cisplatin than with other agents. Furthermore, patients with tinnitus were more likely to have a lower quality of life [ 105 ].…”
Section: Medicines and Materials That Exacerbate Tinnitusmentioning
confidence: 99%
“…In fact, it is well documented that hearing loss, tinnitus, and persistent imbalance retain a negative effect on mental well-being and QoL, having a strong association with the onset and the sustaining of depression and self-isolation. 1 Ototoxicity is a feature shared among some of the drugs proposed for the SARS-CoV-2 treatment. In particular, chloroquine and hydroxychloroquine have been widely promoted and used during the pandemic; 2,3 however, in the past, data in the literature have suggested that in many treated cases side effects such as sensorineural hearing loss, tinnitus, and/or persistent imbalance were common.…”
Section: Dear Editormentioning
confidence: 99%
“…In fact, it is well documented that hearing loss, tinnitus, and persistent imbalance retain a negative effect on mental well-being and QoL, having a strong association with the onset and the sustaining of depression and self-isolation. 1 …”
mentioning
confidence: 99%